Real-world outcomes and prognostic factors in primary mediastinal B-cell lymphoma: a multicenter study of 157 patients - Kucukyurt, Selin; Koca, Oguzhan; Terzi Demirsoy, Esra; Akin, Serkan; Dogan, Ali; Goren, Deniz; Eskazan, Ahmet Emre (Springer, 2025)
Primary mediastinal B-cell lymphoma (PMBCL) is a rare and distinct subtype of non-Hodgkin lymphoma. No consensus exists on optimal frontline treatment, and the use of R-CHOP +/- radiotherapy (RT) and DA-EPOCH-R +/- RT remains common, yet comparative real-world data are limited. In our multicenter retrospective study, we analyzed PMBCL patients, stratified by the first-line therapy (R-CHOP-21 +/- RT or DA-EPOCH-R +/- RT). Primary outcomes were complete response (CR) rate, progression-free survival (PFS), and overall survival (OS), alongside assessment of treatment-related toxicities and prognostic factors for PFS and OS. We included 157 patients [R-CHOP +/- RT group (n = 80) and DA-EPOCH-R +/- RT group (n = 77)] with a median age of 31 years, of whom 68.2% were female. CR rates were similar for R-CHOP +/- RT (75%) and DA-EPOCH-R +/- RT (76.6%). RT use was higher in the R-CHOP group (41.2% vs. 19.5%, p = 0.002). DA-EPOCH-R had significantly higher toxicity (29.9% vs. 16.2%, p = 0.033). The median follow-up of the entire cohort was 29 months with 2-year PFS and OS rates of 73.9% and 83.6%, respectively. Also, PFS and OS did not differ between regimens. In patients achieving CR with R-CHOP, RT omission did not impact survival. Multivariate analysis identified older age, poor performance status, superior vena cava syndrome and splenic involvement as independent OS predictors, while pericardial effusion, splenic involvement and hemoglobin < 10.5 g/dL were linked to inferior PFS. R-CHOP-21 +/- RT and DA-EPOCH-R +/- RT provide comparable efficacy in PMBCL. Due to the higher toxicity of DA-EPOCH-R, for those achieving CR following R-CHOP, selective RT omission may be a reasonable alternative. Established and disease-specific prognostic factors should guide individualized treatment strategies.
Keywords: AaIPI; DA-EPOCH-R; IPI; NCCN-IPI; Primary mediastinal B-cell lymphoma; PMBCL; R-CHOP; Radiotherapy